Consumers’ coping strategies when they feel negative emotions in the face of forced deconsumption during the Covid-19 pandemic lockdowns - Ertz, Myriam; Tandon, Urvashi; Yao Quenum, Gautier G.; Salem, Mohammed; Sun, Shouheng (Frontiers in Psychology, 2022)
Introduction This paper explores consumers’ coping strategies when they feel negative emotions due to forced deconsumption during the Covid-19 pandemic lockdowns. Methods The tool used for data collection is the questionnaire. It was made using the LimeSurvey software. A total of 621 complete observations were analyzed. Results The findings demonstrate that anger positively influences the activation of seeking social support, mental disengagement, and confrontive coping strategies. Besides, disappointment activates mental disengagement but only marginally confrontive coping and not behavioral disengagement. Furthermore, regret is positively related to confrontive coping, behavioral disengagement, acceptance, and positive reinterpretation. Finally, worry positively impacts behavioral disengagement, self-control, seeking social support, mental disengagement, and planful problem-solving. Discussion The study’s originality lies in its investigation of consumers’ coping strategies when experiencing negative emotions due to forced deconsumption in the context of the Covid-19 pandemic.